The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1445-2197.2006.03879.x
|View full text |Cite
|
Sign up to set email alerts
|

Will the Dilemma of Evidence‐based Surgery Ever Be Resolved?

Abstract: Exponents of evidence-based medicine do not undermine the importance of clinical expertise and skills, but they emphasize that decision-making in medicine should be based on the best available evidence derived from the systematic analysis of observations made in an objective, unbiased and a reproducible fashion. The randomized controlled trial (RCT) is the most scientifically rigorous means of hypothesis testing in epidemiology. Discrepancies between established surgical and other interventions and best availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…The scholar and librarian work through the patient problem and develop a searchable questionoften using the patient/problem, intervention, comparison, outcome (PICO) format-as well as search strategies. The practice of evidence-based surgery can be problematic; for example, randomized controlled trials are difficult to conduct in many surgical areas due to ethical and technical issues [15,16]. Scholars quickly become aware of these limitations and are encouraged to look for the best available levels of evidence when searching the surgical literature for patient care information.…”
Section: Program Objectivesmentioning
confidence: 98%
“…The scholar and librarian work through the patient problem and develop a searchable questionoften using the patient/problem, intervention, comparison, outcome (PICO) format-as well as search strategies. The practice of evidence-based surgery can be problematic; for example, randomized controlled trials are difficult to conduct in many surgical areas due to ethical and technical issues [15,16]. Scholars quickly become aware of these limitations and are encouraged to look for the best available levels of evidence when searching the surgical literature for patient care information.…”
Section: Program Objectivesmentioning
confidence: 98%
“…1 Only 5% of articles published in three major surgical journals in 1990 were RCTs, and of those a large proportion were found to lack the power to even detect large differences in therapeutic effects at a statistically significant level. 6 Of the remainder, a large proportion utilised poor analytical and methodological techniques. Rothoerl et al have suggested that a high proportion of neurosurgical publications have only a low level of evidence.…”
Section: Education In Research Methodologymentioning
confidence: 99%
“…There are many examples of guidelines that have been shown to reduce mortality and morbidity in surgical patients. 6 2.2. 'Surgery is not amenable to EBM because it is just as much an art as it is science'…”
Section: 'Ebm Does Not Take Into Account Individual Patients'mentioning
confidence: 98%
See 2 more Smart Citations